Crustacean microcoprolites from the Upper Jurassic-lower cretaceous of the Neuqun Basin, Argentina: Systematics and biostratigraphic implications - Kietzmann, Diego Alejandro (2010)
As a result of a microfacial study in the outer and middle ramp deposits of the Vaca Muerta Formation (lower Tithonian-upper Valanginian), four ichnotaxa of crustacean microcoprolites are described: Palaxius azulensis Kietzmann isp. nov., Palaxius caracuraensis Kietzmann isp. nov., Helicerina? isp. A. aff. Helicerina siciliana and Helicerina isp. B. They represent one of the first records of crustacean microcoprolites for the Neuqun Basin and Argentina. Helicerina is reported for the first time from the Upper Jurassic and Lower Cretaceous of South America. It is inferred that Palaxius ichnospecies were produced by callianassids, while Helicerina ichnospecies could be produced by decapods of Mecochiridae, Erymidae, and/or Nephropidae affinity. Two assemblages of crustacean microcoprolites are recognised, a middle Tithonian to lower Berriasian Palaxius-dominated assemblage and an early to late Valanginian Helicerina-dominated assemblage.